2016
DOI: 10.1371/journal.pone.0152088
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Curative Effects between Femtosecond Laser-Assisted Cataract Surgery and Conventional Phacoemulsification Surgery: A Meta-Analysis

Abstract: PurposeTo compare the outcomes of femtosecond laser-assisted cataract surgery (FLACS) with those of conventional phacoemulsification surgery (CPS) for age-related cataracts.MethodsA comprehensive literature search of PubMed, EMBASE, and the Cochrane Controlled Trials Register was conducted to identify randomized controlled trials (RCT) and comparative cohort studies comparing FLACS with CPS. Endothelial cell loss percentage (ECL%), central corneal thickness (CCT), corrected and uncorrected distant visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 51 publications
3
32
0
4
Order By: Relevance
“…A meta-analysis of FLACS vs CPS performed by Chen et al, identified 9 randomised controlled trials (RCTs) 1,2,[5][6][7][8][9][10][11][12][13] . Overall, they found that FLACS significantly reduced effective phacoemulsification time (EPT) compared to CPS.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of FLACS vs CPS performed by Chen et al, identified 9 randomised controlled trials (RCTs) 1,2,[5][6][7][8][9][10][11][12][13] . Overall, they found that FLACS significantly reduced effective phacoemulsification time (EPT) compared to CPS.…”
Section: Introductionmentioning
confidence: 99%
“…Although most cataract patients achieve decent recovery, unfortunately, in a complex disease environment, cataract surgery with phacoemulsification and lens implantation leads to larger endothelial cell loss in diabetic corneas 14 18 . Furthermore, the corneal endothelium can be adversely affected by surgery due to factors like lens nuclear sclerosis, effective phacoemulsification time (EPT), phacoemulsification energy, and IOL implantation 15 , 19 – 21 . These factors coupled with the effect of DM indicate a great risk of long-term endothelium cell dysfunction with decompensation and the development of bullous keratopathy 22 .…”
Section: Introductionmentioning
confidence: 99%
“…There are disturbances in cell migration which results in poor healing. 10,11 Clinical and refractive outcomes of surgery vary among surgeons due to manual creation of incision and phacoemulsification. The primary outcome defining the success of surgery is the visual acuity.…”
Section: Introductionmentioning
confidence: 99%